2017
DOI: 10.1002/aic.15694
|View full text |Cite
|
Sign up to set email alerts
|

Performance and kinetics of membrane and hybrid moving bed biofilm‐membrane bioreactors treating salinity wastewater

Abstract: A pilot‐plant membrane bioreactor (MBR) and two pilot‐plant hybrid moving bed biofilm reactor–membrane bioreactors (MBBR–MBRs), divided into three aerobic and one anoxic chambers, were started up for the treatment of salinity‐amended urban wastewater. The MBBR–MBR systems worked with and without carriers in the anoxic zone (MBBR–MBRanox and MBBR–MBRn/anox, respectively). The systems were operated from start‐up to stabilization, showing high removal of organic matter—a maximum of 90% chemical oxygen demand and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Even though it has been observed that attached biofilms in MBBR‐MBR systems can adapt to salinity, the introduction of saline influent on a steady‐state system operating for the treatment of regular‐salinity urban wastewater showed a decrease of attached biofilm in concentrations of 1000 mg L ‐1 . Accordingly, the inability of the microbial communities in the salinity‐amended urban wastewater led to difficulties for the formation of attached biofilm to hybrid MBBR‐MBR systems started‐up using constant salinity or variable‐salinity urban wastewater has been reported previously …”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Even though it has been observed that attached biofilms in MBBR‐MBR systems can adapt to salinity, the introduction of saline influent on a steady‐state system operating for the treatment of regular‐salinity urban wastewater showed a decrease of attached biofilm in concentrations of 1000 mg L ‐1 . Accordingly, the inability of the microbial communities in the salinity‐amended urban wastewater led to difficulties for the formation of attached biofilm to hybrid MBBR‐MBR systems started‐up using constant salinity or variable‐salinity urban wastewater has been reported previously …”
Section: Resultsmentioning
confidence: 94%
“…For a scenario of influent variable salinity with 6.5 mS cm −1 as maximum, the heterotrophic r su (4.57–24.60 mgO 2 L −1 h −1 ) was lower than that of 4.5 mS cm −1 (9.03–47.17 mgO 2 L −1 h −1 ) but similar to that of 8.5 mS cm −1 (7.23–26.01 mgO 2 L −1 h −1 ), while the autotrophic r su (0.59–14.26 mgN L −1 h −1 ) was higher for the 4.5 mS cm −1 case (2.87–52.10 mgN L −1 h −1 ) and similar between the 6.5 and 8.5 mS cm −1 (2.88–18.49 mgN L −1 h −1 ) scenarios . These results suggested that maximum influent salinity actively affects the r su of both heterotrophic and autotrophic biomass, which become inhibited when maximum salinity reaches a certain threshold.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations